SOME DIRECTIONS OF ENSURING THE FINANCIAL STABILITY OF ENTERPRISES - Muftaydinov Bobur Kiyomitdinovich (Scholar Express Journals, 2023)
The article examines some possibilities and directions for ensuring the financial stability of enterprises. It also mentions the relevance of the topic and the Decrees and Decisions of the President of the Republic of Uzbekistan related to the topic. Advances in field research are noted. It also lists 14 options available to ensure the financial stability of enterprises and directions for their use.
Keywords: Stability; sustainable growth; financial stability; economic opportunities